Bond Strength of Resin Composite Posts Placed in Primary Teeth: A Comparison of Adhesive Systems - Mohammad Aun Ali Mehdi, Zain Noor, Nabiya Shahroz, Mariam Adnan, Irha Hussain Zaidi, Sumayya Surti (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: In this study, researchers used two different adhesives to determine which ones had the strongest push-out connection between resin composite posts and primary teeth’s intracanal dentin. Methods: Fifty primary lateral incisors were split into two groups (n = 25) and treated with either Adper Single Bond 2 (ASB group) or Clearfil SE Bond 2 (CSE). Resin composite was used to fill the canal in the root’s coronal one-third. A universal testing equipment was used to conduct the push-out evaluation. The data was analyzed using t-test. Results: Strengths of push-out bonds were found to be significantly different amongst the two groups using t-test (p=0.000). The mean±S.D push-out bond strength of the samples in ASB group was 8.41±4.83 Mpa, while mean±S.D push-out bond strength of the samples in CSE group was 14.21±4.03 Mpa. Most failures were adhesive, and there was no difference (p=0.327) in the fracture mode distribution between bonding agents. Conclusion: In terms of push-out bond strength, CSE group was clearly superior to ASB group. When placing resin composite posts in primary anterior teeth, it is advised to utilize a universal adhesive system and self-etch adhesives from the sixth generation. Due to their simplicity of use, reduced technical sensitivity, and reduced number of required clinical processes, bonding agents may be a desirable choice for repairing primary teeth with short resin composite posts. Keywords: Adhesive system, bond strength, primary teeth, resin composite